The role of oral flora in the development of chemotherapy‐induced oral mucositis. (4th February 2014) - Stringer, Andrea M.; Logan, Richard M.
<x xml:space="preserve">Abstract</x> Chemotherapy‐induced mucositis is considered to be a major oncological problem, caused by the cytotoxic effects of cancer chemotherapy. In the last 10 years, there have been significant advances in the understanding of mucositis pathobiology. At the basic level, it is now well‐understood that it is not just an epithelial process, but rather a complex interaction between epithelial and connective tissue compartments. There is also potential interaction between the oral microenvironment and the development of mucositis. Changes occur in the resident oral flora (commensal) throughout cancer treatment, and it is conceivable that these organisms and changes that occur may have an influence on the development of mucosal toxicity associated with cancer treatment. The aim of this review was to examine the potential contributions of oral microflora in the pathobiology of mucositis and identify pathways and interactions that could be targeted for therapeutic management of mucositis.